How not to fail in competition? Coping with pressure in sports - Bilski, L.; Kasza, W. (Studies in Sport Humanities, 2015)
Pressure in sporting competition is quite common; however, it can have either a positive or negative influence on an athlete`s performance. Once the athlete starts seeing pressure as negative, their performance quality may drop below the expected level. The purpose of this study is to identify the optimal ways of coping with pressure. Various psychological theories regarding attention or social behaviour have been reviewed. Two tools were used in empirical research. The Sport Pressure Checklist by Rushall and Sherman [1987] deals with sources of pressure in the sporting environment. Pressure can be evaluated as positive, negative, or neutral. Sources of pressure were compared with psychological coping capabilities using the Athletic Coping Skills Inventory by Smith, Schutz, Smoll and Ptacek [1995]. Both tools were translated into Polish and adapted by the authors of this study. Research was conducted amongst volleyball players representing different levels of professionalism and experience. The results show that individual coping styles differ between athletes. There is a relationship between coping styles and perceived sources of pressure amongst athletes. The purpose of this study was to create personalized best practices for teachers, coaches, and the athletes themselves that would enable them to cope with and react to heavy pressure in the most optimal way.